The Changing Roles of GPS Tracking in Dementia Care - Meyer, Astrid (Tidsskrift for Forskning i Sygdom og Samfund, 2024)
Global Positioning System (GPS)-tracking is increasingly used to prevent and manage wandering in Danish dementia care. In this article, I follow the first-hand experiences of a woman using GPS-tracking to care for her husband with Alzheimer’s at home and after he moves into a nursing home. In doing so, I trace how the GPS-tracker plays many different roles as it is used for different purposes. To conceptualise these changes, I draw on the idea of care arrangements (López Gómez, 2015; Thygesen & Moser, 2010), and understand GPS-tracking as being a part of ever-changing constellations of heterogeneous elements allowing for particular possibilities and restraints in care. I show how GPS-tracking is a dynamic technology, able to change along with care arrangements. Making GPS-tracking change role does, however, also add tensions and new expectations, which means it not only is shaped by care arrangements but also shapes them. Based on this co-shaping, I argue that GPS-tracking is a ’sticky’ technology that clings to the care arrangement. The idea of ’stickiness’ is furthermore supported by the way GPS-tracking makes itself seem necessary as it articulates risks in particular ways. By drawing on Buch’s notion of care as generative labour (2018), I point to how GPS-tracking produces new responsibilities, which require alert carers. In exploring these tensions and changing roles I aim to add nuance to the use of GPS-tracking and how this technology both can cause and indicate broader changes in dementia care.